The effect of MDP-based primer on shear bond strength of various cements to two different ceramic materials. Issue 10 (19th May 2017) - Pak Tunc, Elif; Ozer, Fusun; Ayyildiz, Simel; Ula, Taylan A.; Sen, Deniz
Abstract: The aim of this study was to determine the effect of 10-methacryloyloxydecyl dihydrogen phosphate (MDP)-based primer on the shear bond strengths of thermally aged self-adhesive and conventional adhesive resin cements and zinc phosphate cement to zirconia and lithium disilicate substructures. Sixty zirconia (Z) and 60 lithium disilicate (L) disk specimens were cut from ceramic blocks. Each group was divided into six subgroups ( n  = 10). Half of the specimens of each ceramic group were treated with primer (P) and the other half was remained untreated. Three types of cement were applied: zinc phosphate cement [(ZPC) (Hoffmann Harmonic Shades)]; self-adhesive resin cement [(SAC) (RelyX U200)]; conventional adhesive resin cement [(CAC) (C&B)]. The specimens were subjected to thermal aging procedure for 1 week under 37 °C water bath. Shear bond strength (SBS) was determined using a universal testing machine at a crosshead speed of 1 mm/min. Data were analyzed with three-way (ANOVA). Pairwise comparisons and interactions between groups were analyzed by using Tukey's simultaneous confidence intervals. There was no significant difference between the SBS values of SAC-Z (11, 47 ± 0, 47) and SAC-ZP (11, 39 ± 0, 42) ( p  > 0.05). However, the SBS values of SAC-L (12.34 ± 0, 55) and SAC-LP (12, 50 ± 0, 49) were significantly higher than those of SAC-Z and SAC-ZP ( p  < 0.00). The use of primer significantly increased the SBS value of CAC-ZP (8, 05 ± 0, 55) when compared to the SBS value of CAC-Z (3, 53 ± 0, 41) ( p  < 0.00). Resin cement that contains methacrylate monomers with phosphoric ester functional groups exhibited reliable bond to zirconia. However, the use of an MDP-based primer may not further improve its bond strength.